Usability of Public Play Spaces for Children with Disabilities - Asma Nidaul Haq; Yuko Ito; Natsuka Suyama; Peter Bontje; Hana Hanifah; Kaoru Inoue (Occupational Therapy International)
Purpose. To investigate the usability of public play spaces for children with disabilities by exploring their experiences in accessing and using these spaces and to further discuss recommendations for designing such spaces that are usable for these children. Methods. A hermeneutic phenomenological approach was employed to explore the experience of children with disabilities regarding the public play spaces. Seven children and their caregivers from two inclusive elementary schools in Central Java Province, Indonesia, participated in the study. Online semistructured interviews with the children were held using Zoom, followed by telephonic interviews with their parents. In addition, video recordings of the observation of the children’s participation in the play spaces were gathered. The interview and video observation data were analyzed using van Manen’s hermeneutic phenomenology thematic analysis method. Results. Five themes arose regarding the experiences of children with disabilities of accessing and using the public play spaces: (1) where time appeared to speed up, (2) “I like the tall one … I like extreme,” (3) fostering connectedness, (4) the need for a safe space, and (5) how a play space should be. Conclusion. The public play spaces have meaningful values for the children with disabilities and their family, as they offered the opportunities to play, explore, interact with friends and families, enjoy nature, interact with animals, and learn. However, it is essential to provide a safe space in which children are free from physical and emotional harm, so that they can fully participate with confidence and a sense of autonomy. Nevertheless, it was also found that children, regardless of their abilities, craved risky and challenging play opportunities. This study also highlights the necessity of awareness-raising intervention programs to foster the inclusion of children with disabilities in public play space settings.